Strategi Pendekatan Peran Sebagai Pemimpin Dan Keluarga Yang Diterapkan Kepala Sekolah Untuk Meningkatkan Komitmen Kerja Guru Di Sekolah - Bagus Rachmad Saputra (Kelola: Jurnal Manajemen Pendidikan, 2019)
This study aims to describe the role applied by the principal to improve teacher work commitments. This research was conducted with a qualitative descriptive approach using a multi-site approach at the Baitul Izzah Integrated Islamic Elementary School (SDIT) and the Islamic Elementary School (SDI) Plus Baitul Ikhlas Nganjuk. Research data were obtained from the principal as key informants, teachers, committees, and foundations. Data was collected in the form of structured and unstructured in-depth interviews, participatory observation, and document study. Data sourced from field notes, documents, and interview transcripts that were reduced were then analyzed for validity and credibility tests using triangulation techniques. The results of the study include: 1) the task approach strategy as an obligation that must be completed by the teacher in the context of professional relations; 2) spiritual approach to increasing teacher commitment at school; 3) family approach through active communication to increase teacher work commitment.